Tradução selvagem: autotradução e trânsito entre línguas na poesia de Humberto Ak'abal - Alice Lamounier Ferreira (2021)
The Mayan-Quiché poet Humberto Ak’abal (1952-2019) is considered one of the greatest Guatemalan poets. In 1990, he published his first book, Ajyuq’. El animalero, when he was forty. Currently, it has more than twenty books published and translated into several languages. In this dissertation, his work will be considered from the transit between languages as a central part of his poetic work, operated by wild translation. For this, we will go through Ak’abal's conception of poetry and poet, approaching the shamanic word and the shaman. We will try to understand how a text is conceived as a double.We will see how the double unfolds from three writing strategies: lexical estrangement, entry-poems and translation-poems, and pure sonority as poetry. In Ak'abal's poetry, self-translation becomes a privileged place by bringing into play a complex network of relationships between notions such as the native and the colonizing language, the self and the other, orality and writing, the original and the translation, ritual and history, and the colonial and the post-colonial. The proposals of authors such as Antoine Berman, Haroldo de Campos, Álvaro Faleiros, Gilles Deleuze, Félix Guattari, Claude Lévi-Strauss, Viveiros de Castro and Arturo Arias, Valle Escalante, Mikel Ruiz.